A new airfoil for the supporting struts of smaller-capacity straight-Bladed VAWT - Islam, Mazharul; Amin, M. Ruhul; Ting, David S-K; Fartaj, Amir (2008)
The primary sources of drag for a straight-bladed vertical axis wind turbine (SB-VAWT) are the blades which are also responsible for generating lift. The supporting struts of a SB-VAWT are also responsible for generating additional parasitic drag which reduces the overall power output. It is one of the major disadvantages of the SB-VAWTs as the loss of power due to its effect is proportional to the cube of tip speed ratio. The aim of this paper is to present an alternative airfoil for the shape of the supporting struts of smaller-capacity fixed-pitch SB-VAWTs to reduce the parasitic drag losses. A new airfoil "MI-STRUT1" has been designed which performs better than another available streamlined strut, namely E862, especially at low RN range. Based on the finding it has been proposed that MI-STRUT1 can be considered as a potential candidate for the profile of supporting struts of SB-VAWT for better performance.